Tratamento e reúso do efluente gerado em um processo de pintura industrial por eletrodeposição - Ribeiro, João Carlos (2015)
The use of the wastewater as the water to feed painting systems, associate to environmentand economics availability restrictions, propels the need to create projects focused to reuse of water on industries. The treatment and reuse of wastewater generated at industries has showed an important tool for minimize the problems related of hydric availability, besides offering economic advantages. This work evaluated the effluent generated from a pre-treatment system with nanotechnology and e-coat paint, to enable its reuse as a source of supply on the same painting system. The effluent generated in this process is treated in the ETE by physicochemical and biological processes to meet environmental legislation, and then released in its entirety to the receiving bodies. The characterization of this effluent, after passing through the painting process, showed high levels of conductivity, pH, total solids, oil and grease, surfactants and the presence of bacteria, being necessary to use an additional treatment step with the purpose to make it unable to reuse as water to painting process. The sampling of effluent were performed daily during a period of 20 days. Whitin this process were analyzed the wastewater of tank four, first tank after degrease, tank eight, first tank after the nanoceramic conversion and the mix of tank four with the tank eigth in 50/50 proportion. It was used 4 types of treatment being, coagulation/flocculation, neutralization, filtration with bag filter of 1µm, filtration with activated carbon and their combinations to evaluate the better alternative economic/financial to reuse. After performing the tests, the treatment technology consisted of coagulation/flocculation followed by filtration with bag filter of 1µm and activated carbon filter showed the best result for reuse. Analyzing the parameters after the treatment sequence, was verified that the wastewater of the tank eight, which showed values bellow of the maximum allowed, could returned again to system through a closed circuit, without treatment. Regarding the effluent of tank four, this should be submitted to wastewater recovering system defined before to return to painting system. With the implementation of the reuse system, it is estimated an annual reduction of water consumption of 17.393m³, being the wastewater of tank eight responsible for 61% of this value. Using these two wastewater, the company will have an annual saving which can turn around R$ 258.811,00 considering the water used in the process and the cost to treat this wastewater.